1999
DOI: 10.1038/sj.jhh.1000864
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of hypertension in an un-industrialised rural population of North India

Abstract: Recent studies have indicated a rising prevalence of hypertension in rural and urban areas of India. A population-based survey was carried out during 1994 -1995 in seven rural and non-industrialised villages around RaipurRani block in the state of Haryana, India, to determine the prevalence of hypertension and its associated risk factors. A total of 2559 individuals (86% of the eligible population) in the 16 to 70-year age group were interviewed using a pre-tested structured questionnaire to find out the lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
81
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 9 publications
18
81
5
Order By: Relevance
“…This study showed a higher incidence of anemia with lower BMI. Similar observation was found by authors such as Malhotra et al [9] and Bhattacherjee et al [10] that there was a significant correlation between hemoglobin level and BMI. With the increase in BMI, hemoglobin level increases significantly.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study showed a higher incidence of anemia with lower BMI. Similar observation was found by authors such as Malhotra et al [9] and Bhattacherjee et al [10] that there was a significant correlation between hemoglobin level and BMI. With the increase in BMI, hemoglobin level increases significantly.…”
Section: Discussionsupporting
confidence: 79%
“…Most of the people in this study were uneducated hence they are unaware about anemia and its importance. Similar observation was found in previous studies revealed by authors such as Sanjay et al, [5] Vitull et al, [6] Nora [13], and Malhotra et al [9]. Adequate patient counseling about anemia was given to the anemic population.…”
Section: Discussionsupporting
confidence: 78%
“…Association was found in the studies conducted by Malhotra et al with no statistical significance. 15 Khan et al, Gupta et al in their studies showed positive association with smoking and the disease. 12,16 Prevalence of alcohol consumption among the study participants in the present study was 31.1%, and among those who had disease 30.5% gave positive history of alcohol consumption.…”
Section: Resultsmentioning
confidence: 99%
“…It also suggested that 65% of the risk for HTN in women and 78% in men can be related to obesity. The study done in Jaipur urban (both sexes) and rural studies (only males) [17], the Haryana rural study [18], the Chennai urban population study [19] as well as the Bombay executive study [20] have all shown a higher weight and BMI among hypertensive groups.…”
Section: Resultsmentioning
confidence: 99%